Research and application of hydraulic fracturing axial roof cutting technology for gently inclined hard roof based on abrasive jet - Sun, Ruda; Zhao, Zhipeng; Yang, Wei; Li, Hongping (Frontiers in Earth Science, 2024)
In order to explore a new method and mode of gently inclined hard roof treatment, the hydraulic fracturing axial roof cutting technology based on abrasive jet is introduced, and the key technical parameters of abrasive jet axial cutting and fracturing are determined based on indoor experiments and field industrial experiments. Taking the mining of working face under the condition of hard roof in Kuangou Coal Mine as the background, the implementation process and the effect of mining process are tested by means of water pressure gauge, drilling peep and observation well water level observation, mi-croseismic monitoring, support fracture monitoring and coal stress monitoring. The research results show that the key technical parameters of slotting and fracturing are mastered in the axial cutting test of abrasive jet. Wherein the kerf depth is 200 m, the kerf length is 300 m, the kerf pressure is 40–50 mpa, the fracturing pressure is 50–55 mpa, and the fracturing time is 20–30 min. After grooving fracturing, the cracks in the roof strata are effectively generated and expanded, which destroys the integrity of the roof, and the fracturing radius is 10–20 m. During the mining period, compared with the tradi-tional blasting technology, the concentrated area of microseismic events was shifted from 80 m in front of the working face to 130 m after the combined treatment of abrasive jet axial roof cutting and blasting, and the microseismic energy release was mainly small energy events. After the application of abrasive jet axial roof cutting and scour prevention technology in hard roof, the periodic weighting step is obviously reduced, the influence range of mining stress and stress concentration coefficient are obviously reduced, the activity intensity and dynamic load effect of surrounding rock are obviously weakened. The research results provide a basis for effective prevention and control of rockburst disasters under the condition of hard roof.